2011
DOI: 10.1371/journal.pone.0025975
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Palmitate Overload on Nutrient-Induced Insulin Secretion and Autocrine Signalling in Pancreatic MIN6 Beta Cells

Abstract: BackgroundSustained exposure of pancreatic β cells to an increase in saturated fatty acids induces pleiotropic effects on β-cell function, including a reduction in stimulus-induced insulin secretion. The objective of this study was to investigate the effects of chronic over supply of palmitate upon glucose- and amino acid-stimulated insulin secretion (GSIS and AASIS, respectively) and autocrine-dependent insulin signalling with particular focus on the importance of ceramide, ERK and CaMKII signalling.Principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 54 publications
(67 reference statements)
1
34
0
Order By: Relevance
“…A comparable anti-apoptotic role for GPR40/FFAR1 has been suggested previously using the unsaturated fatty acid oleate which also activated ERK1/2 in NIT-1 cells [24]. In contrast to these observations another study associated ERK1/2 phosphorylation with insulin secretion and chronic stimulation of GPR40/FFAR1 with beta cell death [14]. An explanation for the differences could be the use of high concentrations of the MEK inhibitor U0126, which has been found to induce side effects such as increases in the cellular ratios of ADP/ATP and AMP/ATP [25].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A comparable anti-apoptotic role for GPR40/FFAR1 has been suggested previously using the unsaturated fatty acid oleate which also activated ERK1/2 in NIT-1 cells [24]. In contrast to these observations another study associated ERK1/2 phosphorylation with insulin secretion and chronic stimulation of GPR40/FFAR1 with beta cell death [14]. An explanation for the differences could be the use of high concentrations of the MEK inhibitor U0126, which has been found to induce side effects such as increases in the cellular ratios of ADP/ATP and AMP/ATP [25].…”
Section: Discussionsupporting
confidence: 57%
“…Activation of ERK1/2, especially by glucose, has been linked to stimulation of insulin secretion [14]. In contrast, our study showed that a concentration of PD98059 (10 µmol/L), which was sufficient to reverse the effect of glucose on ERK1/2 phosphorylation, significantly augmented glucose-induced insulin secretion in INS-1E cells [13].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Perturbations in CaMKII signaling are observed following palmitate treatment of insulinoma ␤-cells (52). Therefore, changes in CaMKII signaling may contribute to aberrant ␤-cell function following HFD feeding, during the progression of diabetes (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 30% of the population is afflicted by NAFLD and 5-10% of these patients develop non-alcoholic steatohepatitis (NASH), which can progress to cirrhosis and hepatocellular carcinoma [2,3]. Both obesity and insulin resistance are major risk factors for NASH and are characterized by an increase in circulating free fatty acids (FFAs) [4][5][6]. The excess serum FFAs in the context of insulin resistance are transported into hepatocyte by the fatty acid transporter.…”
Section: Introductionmentioning
confidence: 99%